(untitled) (Annals of Medical Research, 2023)
Aim: The association between serum albumin-to-creatinine ratio (sACR) and in-hospital mortality remains unclear in patients with acute coronary syndrome (ACS). In this study we aimed to investigate the prognostic value of sACR in predicting in-hospital mortality in ACS. Materials and Methods: The study was conducted in a single tertiary center. Patients hospitalized with both ST Elevation Myocardial Infarction (STEMI) and Non-STEMI were retrospectively analyzed. The sACR and other clinically related parameters were recorded. The primary outcome was in-hospital mortality. Logistic regression (LR) models were used to investigate the association between sACR and in-hospital mortality. Receiver operating characteristic (ROC) curve was used to find out the cut-off level of sACR. Results: A total of 686 patients with ACS were enrolled, of whom 59 (%8.6) died in-hospital follow-up. The sACR was significantly lower in patients who died in hospital (2.9 (2.3-3.7) vs 3.9 (3.3-4.6)). Multivariable LR analysis showed that sACR is an independent predictor of in-hospital mortality in patients with ACS. Area under the curve value generated by ROC curve analysis was 0.719 (95% CI: 0.656-0.783). The sensitivity of sACR predicting in-hospital mortality was 77.5% with the specificity of 59.3%. Conclusion: In this study, lower sACR on admission was found significantly associated with in-hospital mortality in patients with ACS.